Konsepsi Kegiatan Amal Saleh Solusi Pembentukan Karakter Religius - Ahmad Budiyono; Arif Rahman Hakim; Mohammad Lindu Aji Santoso (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
Charity means deeds (good), actions that bring rewards (according to the teachings of Islam), and which are carried out to do good to society or fellow human beings. While pious means the opposite of evil. So good deeds are all actions according to the instructions of the Qur'an and as-Sunnah which if done can bring benefits to oneself, the group, and the community as a whole. This research is a literature study with a documentary data collection method, using content analysis. The results of the study indicate that good deeds based on sincere and sincere intentions will have an influence and increase as well as moral perfection and increase religious attitudes. Qur'anthethat a holy life, the beauty of the hereafter, and the attainment of the state of closeness (qurb) and encounter (liq?)with Allah the Creator depend on faith and good deeds.Qur'anTheplaces great emphasis on good deeds and only good deeds are the means of happiness and good fortune. The benchmarks and levels of charity piety are in harmony (not contrary) to the Shari'a and Allah's revelation.